2004
DOI: 10.1111/j.0021-8782.2004.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal innervation of the air sacs in a songbird, Taenopygia guttata

Abstract: The air sacs of birds are thin-walled chambers connected to the lung that act as bellows in the ventilatory mechanism. Physiological evidence exists to suggest that they may contain receptors that are innervated by the vagus nerve, but no morphological study has examined the vagal innervation of these putative structures. To do this, we injected the cervical vagus nerve with choleragenoid and examined the innervation of the air sacs using light and confocal microscopy. We identified vagally innervated structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 42 publications
0
16
0
2
Order By: Relevance
“…Structures similar to neuroepithelial bodies have been described in the air sac membranes (Kubke et al, 2004), and recordings from vagal fibers indicate a response of these putative receptors during the inspiratory phase of respiration. This activity is consistent with the air injection experiment, because the injection would generate a brief inspiration-like expansion of the air sac.…”
Section: Introductionmentioning
confidence: 81%
“…Structures similar to neuroepithelial bodies have been described in the air sac membranes (Kubke et al, 2004), and recordings from vagal fibers indicate a response of these putative receptors during the inspiratory phase of respiration. This activity is consistent with the air injection experiment, because the injection would generate a brief inspiration-like expansion of the air sac.…”
Section: Introductionmentioning
confidence: 81%
“…The former are slowly adapting responses to inflation of the respiratory system, insensitive to hypoxia or hypercapnia. They fire throughout inspiration, but the specific location of these receptors is unknown; indeed, they could lie anywhere in the thoracoabdominal cavity, including the air sacs (Kubke et al, 2004). Their contribution to the control of respiratory function is unclear.…”
Section: Peripheral Mechanics Of Breathing In (Song)birdsmentioning
confidence: 99%
“…However, in the only published study of a respiratory muscle in birds (DeWet et al, 1971), very few muscle spindles were found in m. transversus abdominis of chickens. Neuroepithelial body-like receptors have been identified in the air sacs of zebra finches, but their adequate stimuli are unknown (Kubke et al, 2004). …”
Section: Peripheral Mechanics Of Breathing In (Song)birdsmentioning
confidence: 99%
“…These mechanoreceptors are most likely located in the air sac system (Kubke et al, 2004) and probably respond to volume changes, particularly during the inspiratory phase (Ballam et al, 1982;Molony, 1974). In cardinals, an increase in air sac volume by injection of small air pulses into the anterior thoracic air sac during song resulted in decreased EMG activity in the abdominal expiratory muscles (Suthers et al, 2002).…”
Section: Somatosensory Feedbackmentioning
confidence: 99%